2003
DOI: 10.1021/ja0372309
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of α,β-Disubstituted-β-amino Acids

Abstract: Highly diastereoselective and enantioselective addition of N-benzylhydroxylamine to imides 17 and 20-30 produces alpha,beta-trans-disubstituted N-benzylisoxazolidinones 19 and 31-41. These reactions proceed in 60-96% ee with 93-99% de's using 5 mol % of Mg(NTf2)2 and ligand 18. The product isoxazolidinones can be hydrogenolyzed directly to provide alpha,beta-disubstituted-beta-amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(46 citation statements)
references
References 18 publications
(10 reference statements)
2
44
0
Order By: Relevance
“…[a] Finally, the addition to tigloyl derivatives 14 [14] and 15 was studied. These reactions were extremely sluggish, furnishing low yields even with the most reactive 4-chloroaniline (entries 7 and 8).…”
Section: Synthesis Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…[a] Finally, the addition to tigloyl derivatives 14 [14] and 15 was studied. These reactions were extremely sluggish, furnishing low yields even with the most reactive 4-chloroaniline (entries 7 and 8).…”
Section: Synthesis Ofmentioning
confidence: 99%
“…The product was obtained as a white solid (1.64 g, 24 %). R f = 0.35 (Et 2 O) N-(2-Methylbut-2-enoyl)-benzamide (14): [14] The product was obtained as a white solid in 40 % yield. …”
Section: -[D]-n-(but-2-enoyl)-benzamide (2-[d]-4 A)mentioning
confidence: 99%
“…[14] Very recently, they extended the substrates to α,β-disubstituted imide-derived acceptors [Equation (2) in Scheme 5] and found that magnesium triflimide gave optimal enantioselectivity in the presence of the same bisoxazoline (up to 96 % ee). [15] Independently, Cardillo and coworkers discovered that low to moderate ee's (up to 29 % ee) could be obtained in the aza-Michael addition of BnONH 2 to doubly activated acceptors in the presence of a Cu II -box complex [Equation (1) in Scheme 6].…”
Section: Catalytic Asymmetric Aza-michael Reactions Of Hydroxylamine mentioning
confidence: 99%
“…We have previously shown that imides of type 16 are quite reactive and have handles to provide rotamer control. 12 Competition between 3 and 16 shows that the imide 16 is twice as reactive than 3.…”
mentioning
confidence: 99%